Improvement of scarf repair patch shape for composite aircraft structures. Issue 6 (26th April 2023) - Vadean, Aurelian; Abusrea, Mahmoud; Shazly, Mostafa; Michel, Adrien; Kaabi, Abderrahmen; Boukhili, Rachid
ABSTRACT: Scarf patching is the preferred technique for repairing physically damaged aircraft composite structures. The commonly used patch design is a circular conical frustum with a 3°optimized scarf angle. However, for this repair patch design the volume of material removed from the repaired composite panel can be quite large. This paper examines the effects of the different parameters on the stress state in the patch adhesive, such as ply orientation, stacking sequence, ply thickness and scarf angle. It explores an adaptive design of the repair patch for orthotropic materials and composite laminates, using 3D Finite Element Analysis. The design optimization approach is based on the evaluation of a Failure Criterion Index (FCI) and the minimization of its Relative Standard Deviation (RSD). An optimized scarf shape, which takes into account biaxial tensile loading conditions, fiber direction, and stacking sequence, is an elliptical conical frustum that induces a variable scarf angle along the sweeping angle. This design showed that less parent material is removed than that of the circular shape (decreased by up to 41%) and that the shear stress dispersion in the adhesive was significantly reduced (RSD decreased by up to 18%). The optimization method and the improved shapes are presented and discussed with respect to the influencing parameters.